Peanut Allergy: Characteristics and Approaches for Mitigation. Issue 5 (25th June 2019) - Shah, Faisal; Shi, Aimin; Ashley, Jon; Kronfel, Christina; Wang, Qiang; Maleki, Soheila J.; Adhikari, Benu; Zhang, Jinchuang
Abstract: Peanut allergy has garnered significant attention because of the high sensitization rate, increase in allergy, and severity of the reaction. Sufficiently reliable therapies and efficient mitigating techniques to combat peanut allergy are still lacking. Current management relies on avoiding peanuts and nuts and seeds with homologous proteins, although adverse events mostly occur with accidental ingestion. There is a need for hypoallergenic peanut products to protect sensitized individuals and perhaps serve as immunotherapeutic products. Alongside traditional practices of thermal and chemical treatment, novel processing approaches such as high‐pressure processing, pulsed ultraviolet light, high‐intensity ultrasound, irradiation, and pulsed electric field have been performed toward reducing the immunoreactivity of peanut. Covalent and noncovalent chemical modifications to proteins also have the tendency to alter peanut allergenicity. Enzymatic hydrolysis seems to be the most advantageous technique in diminishing the allergenic potential of peanut. Furthermore, the combined processing approach (hurdle technologies) such as enzymatic hydrolysis followed by, or in conjunction with, roasting, high pressure and heat, ultrasound with enzymatic treatment, or germination have shown a significant reduction of peanut immunoreactivity and may emerge as useful techniques in reducing the allergenicity of peanut and other foods. This study represents our current knowledge about the alterations in allergenic properties of peanut via different processing mechanisms as well as evaluating its future potential, geographical based data on increasing sensitization, clinical relevance, eliciting dose, and current management of peanut allergy. Furthermore, the molecular characteristics and clinical relevance of peanut allergens have been discussed.